Напрями удосконалення управління цифровізацією бізнес-процесів сільськогосподарських підприємств в контексті посилення економічної безпеки - Мечет, Артем Олександрович; Mechet, Artem (ЦНТУ, 2024)
Метою кваліфікаційної роботи є розробка теоретико-методологічних принципів та надання практичних рекомендацій щодо управління цифровізацією бізнес-процесів сільськогосподарських підприємств. Досягнення цілей передбачає вирішення таких завдань: встановити сутність та принципи побудови бізнес-процесів сільськогосподарських підприємств; опрацювати особливості цифрового управління бізнес-процесами сільськогосподарських підприємств; системний аналіз показників цифровізації сільськогосподарських підприємств України; системні методи аналізу та оцінки ефективності цифровізації бізнес-процесів сільськогосподарських підприємств; на прикладі ТОВ «Богданівка» оцінити рівень цифровізації бізнес-процесів сільськогосподарських підприємств; розробити заходи щодо вдосконалення цифрового управління бізнес-процесами сільськогосподарських підприємств; запропонувати напрямок удосконалення цифрового управління бізнес-процесами сільськогосподарських підприємств; наочно продемонструвати економічну доцільність впровадження запропонованих заходів. Об’єктом дослідження є цифрове управління бізнес-процесами сільськогосподарських підприємств. Предмет - сукупність теоретико-методологічних засад і практичних рекомендацій щодо управління цифровізацією бізнес-процесів сільськогосподарських підприємств. The purpose of the qualification work is to develop theoretical and methodological principles and provide practical recommendations for managing the digitalization of business processes of agricultural enterprises. Achieving the goals involves solving the following tasks: establishing the essence and principles of building business processes of agricultural enterprises; to work out the features of digital management of business processes of agricultural enterprises; system analysis of digitalization indicators of agricultural enterprises of Ukraine; system methods of analysis and evaluation of the efficiency of digitalization of business processes of agricultural enterprises; using the example of LLL "Bohdanivka" to assess the level of digitization of business processes of agricultural enterprises; develop measures to improve the digital management of business processes of agricultural enterprises; to propose a direction for improving the digital management of business processes of agricultural enterprises; clearly demonstrate the economic feasibility of implementing the proposed measures. The object of the study is the digital management of business processes of agricultural enterprises. The subject is a set of theoretical and methodological principles and practical recommendations for managing the digitalization of business processes of agricultural enterprises.
Directions for improving digitalization of the business processes management of agricultural enterprises in the context of strengthening economic security
Keywords: сільськогосподарське підприємство; цифровізація; бізнес-процеси; управління; agricultural enterprise; digitalization; business processes; management